Constructing fan charts from the ragged edge of SPF forecasts - Todd E. Clark; Gergely Ganics; Elmar Mertens (Deutsche Bundesbank, 2024)
We develop models that take point forecasts from the Survey of Professional Forecasters (SPF) as inputs and produce estimates of survey-consistent term structures of expectations and uncertainty at arbitrary forecast horizons. Our models combine fixed-horizon and fixed-event forecasts, accommodating time-varying horizons and availability of survey data, as well as potential inefficiencies in survey forecasts. The estimated term structures of SPF-consistent expectations are comparable in quality to the published, widely used short-horizon forecasts. Our estimates of time-varying forecast uncertainty reflect historical variations in realized errors of SPF point forecasts, and generate fan charts with reliable coverage rates.
Keywords: E37; C53; 330; Term structure of expectations; uncertainty; survey forecasts; fan charts